Information asymmetry, education signals and the case of ethnic and native Germans - Stephan O. Hornig; Horst Rottmann; Rüdiger Wapler (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyses the effects of education signals for Ethnic Germans and Germans without a migration background (Native Germans). We base our analysis on a sorting model with productivity enhancing effects of education. We compare whether the signalling value differs between the migrants and non-migrants in the German labour market. Starting from the theoretical result that only a separating equilibrium can exist, we find substantial empirical differences between Ethnic and Native Germans with the same formal education level. This empirical analysis is done with a completely new dataset based on administrative data from the German Federal Employment Agency.
Keywords: J24; J31; F22; 330; sorting theory; human-capital theory; returns to education; migration; Bildungsniveau; Signalling; Bildungsertrag; Lohnstruktur; Aussiedler; Theorie; Deutschland